Fatores de virulência e resistência a antimicrobianos de Staphylococcus coagulase-negativo isolados de pacientes com infecção na corrente sanguínea - Silvia Helena Sousa Pietra Pedroso (2018)
Staphylococcus coagulase-negative (SCN) has emerged as major causative microorganisms of nosocomial bloodstream infections. However, studies that investigate the characteristics that underlie their pathogenesis/resistance are limited. Thus, this work aimed to contribute to the definition of genotypic and phenotypic attributes of SCN isolated from clinical samples of five different hospitals in Belo Horizonte, Minas Gerais, Brazil. Therefore, the samples were phenotypically identified using GP 21342 TEST KIT VITEK II and genottipicaly by rep-PCR (GTG)5. The sensitivity to antimicrobial agents was evaluated using the card AST-P5085 according to manufacturer’s recommendations (bioMérieuxVitek®). The hemolytic capacity ofsamples was evaluated through depletion in blood gar and biofilm formation, through congo red agar (CRA) and polystyrene plates. The toxin production was also assessed by the method OSP (optimum sensitive plate) and by VIDAS ® kit (bioMérieux). In relation to genotypic characterization, PCRs were performed for the detection of resistance genes (mecA, blaZ, vanA, ermA, ermB, ermC and aac-aphD); of virulence genes (atlE, icaA, icaB, icaC, sea, sec, sed, tsst-1) of the agr locus - related to quorumsensing- and of the type of SCCmec cassette. Furthermore, hierarchical analyzes, chisquare test and correspondence analysis were performed in order to establish similar profiles of the strains. 59 samples were isolated, and the most prevalent were S. haemolyticus, S. hominis and S. epidermidis. All lineages were typable using the primer (GTG)5 and the PCR products ranged from 250 to 5000 bp. Most of the specimens had a close fingerprint profile. However, variability in the presence of some bands influenced the final cluster analysis and several clusters were formed in the same species With regard to antimicrobial resistance, 86.4% of samples were multidrug resistant, and resistance frequency was higher for drugs: benzylpenicillin, oxacillin, ciprofloxacin, norfloxacin, erythromycin and clindamycin. The genes, also related to resistance, most prevalent were blaZ (78%), ermB (100%) and the type of SCCmec cassette IIIB. Regarding to virulence, most of the samples showed no pattern of hemolysis; however all strains were able to form biofilms in CRA or polystyrene plates, and the most frequent genes were atlE (49%) and icaB (39%). Most of the samples did not produce toxins, but were prevalent for sea genes (76.2%) and tsst-1 30.5%). Regarding the agr locus, 39% of the samples were positive. Six distinct groups were established and almost all the features presented differences in the frequency distribution: only icaC (χ²15 = 3.88; P = 0.57) sed (χ² = 3.98; P = 0.55), film48h (χ² = 16.30; P = 0.36) and ermA (χ² = 7.96; P = 0.16) did not differ. In this group analysis, it was observed relationship between icaB gene and the strong degree of biofilm formation, and in relation to resistance characteristics, the most discriminatory factors were: resistance to linezolid,vancomycin, teicoplanin, trimethoprim/sulfamethoxazole, moxifloxacin; sensitivity to oxacillin and SCCmec type IIIB. In conclusion, the isolated samples in the city of Belo Horizonte have a significant arsenal of virulence/resistance factors, and so, more studies should be conducted to better understand the mechanisms by which the SCN succeed in colonizing and persist in host in order to combat this group of dangerous microorganisms.